Neoplasmas cutâneas em cães diagnosticados no laboratório de patologia veterinária da Universidade Federal de Mato Grosso, Cuiabá, MT - Lima, Samara Rosolem (2016)
The dermatopathology in dogs is an expanding field in veterinary medicine with a growing focus on the histopathological diagnosis of neoplastic diseases in recent years. The aim of this study was to determine the frequency of skin tumors diagnosed in dogs sent to the Pathology Laboratory of the Federal University of Mato Grosso, Cuiabá, Brazil, between 2007 and 2014. All the necropsy and biopsies protocols from Pathology Laboratory were reviewed, and computed the following information: morphological diagnosis, anatomic location, size of tumor, biological behavior of the tumor, age, sex and breed of affected dogs. Statistical evaluation was performed through a descriptive analysis of the database and subsequently was investigated the distribution of frequency of cases and their ratings. An Association between biological behavior and skin tumor size were carried through the square χ2 test. The canine species represented 29.05% of all histopathological and necropsies examinations performed in LPV-UFMT during the study period. A total of 656 skin tumors were diagnosed, which 623 were biopsies and 33 were necropsies. The samples were from 4 mesoregions state. The region south-central (50%) sent the highest number of samples. Affected dogs for skin tumors were between four months to 18 years old. Dogs with breed were more affected by skin tumors (463/663; [70.57%]) compared to mongrel dogs (SRD) (193/663; [29.42%]). Dogs with breed belonged to a group of 37 different breeds, and the breed Pitbull (17.99%), the Boxer (9.75%) and the Poodle (8.72%) were the most prevalent. A total of 40 different types of skin cancer was observed. Among the classification tumors such as mast cell tumors, squamous cell carcinoma, hemangioma and lymphoma were the most frequently observed, comprising 37.8% (248/656) of all diagnosed skin tumors. Among the types of tumors observed, 253/441 (57.4%) had benign biological behavior and 188/441 (42.6%) had malignant behavior indicating a difference in the ratio between the various sizes of tumors and their biological classification (p = 0.0008206) indicating a high occurrence for benign tumors less than 1 cm in diameter and a high incidence of malignant tumors with size of 3-5cm